Perbandingan Efek Pemberian Bioinsektisida dan Ekstrak Kompos terhadap Produksi Padi Ratun dan Populasi Serangga Hama - Herlinda, Siti; Kusuma, Amarilisa; ., Suwandi; Wijaya, Andi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
The advantages of ratooning rice are to save water, cost production, labor, preparation time for planting and harvesting, but the ratooning productivity is still low. This research aimed to study the effect of the bioinsecticide and compost extract on ratooning rice production and insect populations. The ratooning rice was applied by bioinsecticide, compost extract, and combination of bioinsecticide and compost extract with dose 2 L ha-1 per application, respectively. Data of agronomic variables were statistically analyzed using analysis of variance, whereas insect pest population data were analyzed using Chi Square test. The seedling height of ratoon applied by compost extract was the highest among treatments. The number of productive tillers per clumps and rice production on plot applied by compost extract were higher than the insecticide treatment. At the age of 17 day-ratooning rice, application bioinsecticide reduced the population of insect pests, such as Ciccadulina bipunctata, Recilia dorsalis, Nilaparvata lugens, and Nephotettix nigropictus. Thus, application of compost extract tended to improved the growth and production of the ratooning rice, while the bioinsecticide decreased the insect pest population.Keywords: Beauveria bassiana, rice growth, production